Informatização e gamificação de testes cognitivos para avaliação psicológica - Rodrigues, Samuel Pires (Universidade Federal de São Carlos, 2023)
In recent times, the idea of bringing or creating psychological tests for the online modality has been growing more and more. The present project is part of this problem, turning to the field of study of cognitive assessment. For the creation of the tests, gamification principles were added to the psychological tests in order to make the activities carried out in the tests more playful, attractive and positive for the test taker. In this sense, computerized tests were created on the constructs of (attention, spatial reasoning, numerical reasoning, working memory, thought flexibility, vocabulary extension). A total of 16,314 people over 18 years of age participated in this research and answered the tests in a spiral fashion, with other tests planned to assess related constructs. Finally, it was possible to observe evidence of validity and psychometric parameters of the tests that make up the battery, along with the comparison between different test use platforms, resulting in a set of psychological tests that can help facilitate cognitive assessment in different contexts.
Computerization and gamification of cognitive tests for psychological assessment
Keywords: Avaliação psicológica; Avaliação psicológica online; Gamificação; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA